THE ROLE OF ESG PRINCIPLES IN ATTRACTING INSTITUTIONAL INVESTORS IN CORPORATE GOVERNANCE - Mirzahmedova Durdona Murodovna; Salohitdinova Durdona Faxriddinova (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Institutional investors — such as pension funds, insurance companies, and investment funds — play a crucial role in promoting transparency, accountability, and efficiency in corporate governance. In Uzbekistan, their growing presence since 2017 has significantly influenced how companies are managed and monitored. This paper explores how institutional investors contribute to improving governance standards, increasing shareholder activism, and attracting foreign investment. It also evaluates the challenges they face, including limited market infrastructure and regulatory gaps. The findings suggest that institutional investors are becoming one of the main drivers of corporate reform in Uzbekistan, but further development of the legal and financial system is essential to maximize their impact.